The impact of ICTs on women's economic empowerment - Dagmara Nikulin (Gdańsk University of Technology, Faculty of Management and Economics, 2016)
It is widely argued that ICTs enable the inclusion of low-skilled and traditionally marginalized groups, such as women, people with disabilities, and workers at the base of the pyramid (BoP), in the labor market. In this paper, we investigate the determinants of female participation in the labor market in developing countries with a focus on the impact of the use of ICTs on female labor force participation. We conduct a panel study analysis for 60 developing countries in the time period 2000–2014. Our results confirm that there is rather a positive impact from the use of ICTs on female labor force participation in developing countries. Moreover, we show that gross national income (GNI) per capita, fertility rates and income inequalities influence to some extent the level of women's engagement in the labor market. Our results are robust against different control variables, as well as different ICT proxies.
Keywords: O11; O33; J21; 330; ICTs; female labor force participation; panel data; development level; income inequalities